Zebrafish STAT6 negatively regulates IFNφ1 production by attenuating the kinase activity of TANK-binding kinase 1. (February 2017) - Li, Shun; Lu, Long-Feng; LaPatra, Scott E.; Chen, Dan-Dan; Zhang, Yong-An
Abstract: The aquatic spring viremia of carp virus (SVCV) causes significant mortality in common carp ( Cyprinus carpio ), and TBK1 plays a crucial role in the retinoic acid-inducible gene I (RIG-I)-like receptor (RLR) system by phosphorylating its substrates to induce type I interferons (IFNs) and cellular antiviral responses. In this study, we report that zebrafish STAT6 is induced during SVCV infection and reduces IFNφ1 expression by suppressing TBK1 phosphorylation. A typical IFN stimulatory response element (ISRE) motif was found in the promoter region of zebrafish STAT6, and zebrafish STAT6 transcription was significantly upregulated in the early stages of virus infection. Overexpression of STAT6 interfered with IFNφ1 promoter activity in response to SVCV infection. Additionally, TBK1-, but not MITA-mediated activation of the IFNφ1 promoter was impaired by STAT6. Co-immunoprecipitation and Western blot experiments indicated that MITA and IRF3 were significantly phosphorylated by TBK1, and that the N-terminal kinase domain of TBK1 was critical in this process. In the final step, STAT6 interacted with the N-terminal kinase domain of TBK1 causing dephosphorylation, which resulted in reductions in the phosphorylation of IRF3 and the production of IFNφ1. These results indicate that fish STAT6 can attenuate the kinase activity of TBK1, leading to suppression of IFNφ1 expression which may in turn facilitate virus replication. Highlights: Zebrafish STAT6 interacts with MITA and TBK1. Zebrafish STAT6 decreases the kinase activity of TBK1. Zebrafish STAT6 negatively regulates TBK1-mediated activation of IFNφ1. Zebrafish STAT6 facilitates virus replication by suppression of IFNφ1.